THE EFFECT OF BUSINESS RESCUE’S MORATORIUM ON PROPERTY BELONGING TO THE COMPANY OR IN ITS LAWFUL POSSESSION AND THIRD- PARTY CONTRACTS - Simphiwe P Phungula (Obiter, 2024)
The rights of both company and property owner have been a burning issue when a company embarks on business rescue proceedings. This issue has been plagued by difficulties with the interpretation of “moratorium” as found in section 133(1) of the Companies Act 71 of 2008. Property owners who have concluded contracts of lease or instalment sale with a company constantly find themselves in difficult positions when the company commences business rescue proceedings. These difficulties include, inter alia, the business rescue practitioner’s cancelling of agreements between the property owner and the company, and the associated procedure; the failure of the company to pay in accordance with the agreements and the property owners’ recourse/cause of action; and the effect of a moratorium on those properties. This article therefore deals with the competing legal and commercial interests, including rights, of both company and property owners when a company has commenced business rescue proceedings.